PENGARUH ELECTRONIC WORD OF MOUTH TERHADAP MINAT BELI: PERAN MEDIASI CITRA MEREK - Aditya Fadzri Kusuma; Tony Wijaya (Jurnal Fokus Manajemen Bisnis, 2022)
This study aims to determine the effect of Electronic Word of Mouth (E-WOM) on purchase intention through brand image. This research is quantitative research with a survey method. The population of this study are a customer of Compas Shoes who are domiciled in the Special Region of Yogyakarta. The sampling technique used purposive sampling with 164 people as respondents to the online survey. The data analysis techniques used to answer the hypothesis are simple regression analysis, hypothesis testing, and the Sobel test. The results of this study indicate that: (1) There is a positive and significant effect of E-WOM (Electronic Word of Mouth) on Purchase Intention. (2) There is a positive and significant effect of E-WOM (Electronic Word of Mouth) on Brand Image. (3) There is a positive and significant effect of Brand Image on Purchase Intention. (4) There is a positive and significant effect of E-WOM (Electronic Word of Mouth) on Purchase Intention through Brand Image as mediating variable.